Optimization of the Separation and Validation Method for Ginsenoside Re and Ginsenoside Rg1 Compounds in Panax Ginseng Powder Extract Using the HPLC Method: A Systematic Literature Review - Marzella Dea Rossardy; Azminah (Postgraduate, University of Mataram, 2024)
The analytical methods used to analyze ginsenoside compounds include TLC, HPTLC, HPLC, UPLC, GC and MS. The HPLC method is the most widely used analytical technique with various combinations of UV detection or with ELSD. The HPLC method is a method of separating and purifying chemical compounds or medicinal compounds. To study new information from optimization for the separation of ginsenoside Re and ginsenoside Rg1 compounds, then validate the analytical method to show that the method provides accurate results in accordance with the requirements. The data and information used in this review article come from national and international journals. The data and information search method was carried out using the literature research method. keywords: